'Paradise adrift': Sustainable Rural Tourism, gentrification and migration in the territorial dispute (San Miguel de Allende, Mexico) - Giraldo-Flórez, Luisa Fernanda (2023)
The objective of the research was to understand the potential of rural tourism (TRS) in Jalpa, considering the challenges and opportunities in a context of rural gentrification and migration to the United States that threaten its identity and local sustainability. Given the sociocultural topic under study, the qualitative research approach applied from the Participatory Action Research design was applied. Seven key actors were chosen as a sample (leaders, tourism entrepreneurs and women heads of family). Participatory Action Research as a strategy to develop capacities. For data collection, interview protocols and questionnaires were applied in three workshops. Likewise, making field diaries, cartographies, recording interviews and taking photographs. The main finding warns how the phenomenon of deterritorialization and migration promotes cultural uprooting and the loss of traditional practices, negatively affecting the tourist offer. It is concluded that Jalpa indeed has a sui generis potential to undertake the TRS, where the commitment must be the promotion of participatory management strategies, communal participation and the preservation of traditions and heritage.